2023
DOI: 10.1177/00333549231176000
|View full text |Cite
|
Sign up to set email alerts
|

General Mental Health, Loneliness, and Life Satisfaction in the Context of COVID-19 Policies: A 2-Year Cohort Study in the Netherlands, April 2020–January 2022

Abstract: Objective: Although the COVID-19 pandemic has affected mental health, understanding who has been affected most and why is incomplete. We sought to understand changes in mental health in the context of transmission numbers and pandemic (social) restrictions and whether changes in mental health varied among population groups. Methods: We analyzed data from 92 062 people (aged ≥16 years and able to read Dutch) who participated in the Corona Behavioral Unit cohort study at the National Institute for Public Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We cannot discount that some individual's mental health may have been affected badly, but this medium-term null effect would imply that others equally flourished from lockdowns if that were the case. The same lockdown resilience has been observed in Europe (Danielsen et al, 2023;Van den Boom et al, 2023). While we acknowledge that no doubt for some lockdowns had a significant effect, the evidence from overall mortality over the time of COVID-19 and since, and the mental health sequelae specifically to lockdown periods, rather than other COVID impacts, do not indicate that lockdowns were either a 'deadly policy option' or even had significant medium-term mental health consequences.…”
supporting
confidence: 62%
“…We cannot discount that some individual's mental health may have been affected badly, but this medium-term null effect would imply that others equally flourished from lockdowns if that were the case. The same lockdown resilience has been observed in Europe (Danielsen et al, 2023;Van den Boom et al, 2023). While we acknowledge that no doubt for some lockdowns had a significant effect, the evidence from overall mortality over the time of COVID-19 and since, and the mental health sequelae specifically to lockdown periods, rather than other COVID impacts, do not indicate that lockdowns were either a 'deadly policy option' or even had significant medium-term mental health consequences.…”
supporting
confidence: 62%
“…We found that younger participants (under 40s and even more so with the under 26 age group) reported increasingly higher levels of loneliness throughout the pandemic compared to older participants, particularly in times when COVID-19 preventive measures were stricter [ 17 ]. Younger participants were also more likely to report both positive (eg, working from home) and negative effects (eg, impact on social life) [ 18 ].…”
Section: Findings To Datementioning
confidence: 99%
“…We used individual-level data from the Corona Behavioural Unit Covid-19 Cohort, a dynamic cohort study conducted between April 2020 and September 2022 among the Dutch population by the National Institute for Public Health and The Environment (RIVM) (van den Boom et al, 2023). We used data up until round 18 for distancing (conducted in January 2022) and round 19 for handwashing (conducted March 2022), because after these moments, the Dutch government no longer included these measures in their behavioural policy.…”
Section: Datamentioning
confidence: 99%